Climate change induces shifts in coastal Baltic Sea surface water microorganism stress and photosynthesis gene expression - Seidel, Laura; Broman, Elias; Ståhle, Magnus; Bergström, Kristofer; Forsman, Anders; Hylander, Samuel; Ketzer, Marcelo; Dopson, Mark (Frontiers in Microbiology, 2024)
The world's oceans are challenged by climate change linked warming with typically highly populated coastal areas being particularly susceptible to these effects. Many studies of climate change on the marine environment use large, short-term temperature manipulations that neglect factors such as long-term adaptation and seasonal cycles. In this study, a Baltic Sea 'heated' bay influenced by thermal discharge since the 1970s from a nuclear reactor (in relation to an unaffected nearby 'control' bay) was used to investigate how elevated temperature impacts surface water microbial communities and activities. 16S rRNA gene amplicon based microbial diversity and population structure showed no difference in alpha diversity in surface water microbial communities, while the beta diversity showed a dissimilarity between the bays. Amplicon sequencing variant relative abundances between the bays showed statistically higher values for e.g., Ilumatobacteraceae and Burkholderiaceae in the heated and control bays, respectively. RNA transcript-derived activities followed a similar pattern in alpha and beta diversity with no effect on Shannon's H diversity but a significant difference in the beta diversity between the bays. The RNA data further showed more elevated transcript counts assigned to stress related genes in the heated bay that included heat shock protein genes dnaKJ, the co-chaperonin groS, and the nucleotide exchange factor heat shock protein grpE. The RNA data also showed elevated oxidative phosphorylation transcripts in the heated (e.g., atpHG) compared to control (e.g., atpAEFB) bay. Furthermore, genes related to photosynthesis had generally higher transcript numbers in the control bay, such as photosystem I (psaAC) and II genes (psbABCEH). These increased stress gene responses in the heated bay will likely have additional cascading effects on marine carbon cycling and ecosystem services.